Inside Cover: Tracking Live‐Cell Response to Hexavalent Chromium Toxicity by using Scanning Electrochemical Microscopy (ChemElectroChem 4/2017). Issue 4 (20th March 2017) - Henderson, Jeffrey D.; Filice, Fraser P.; Li, Michelle S. M.; Ding, Zhifeng
Abstract : The Inside Cover picture shows changes in the membrane permeability of single live bladder cells, in response to dicromate. The measurements are neither destructive nor invasive, owing to the nature of scanning electrochemical microscopy (SECM). More details can be found in the Article by Z. Ding and co‐workers onpage 856 in Issue 4, 2017 (DOI:10.1002/celc.201600783 ).